SCIENTIFIC AND THEORETICAL FOUNDATIONS FOR ENSURING ECONOMIC GROWTH IN THE REGION - Aminov , Fazlitdin (THE INNOVATION ECONOMY, 2024)
This article presents the scientific and theoretical definitions given by economists of the concepts of "economic growth", "economic potential" and their comparative analysis, the importance of regional potential in ensuring sustainable economic development and economic growth, its main elements are highlighted. Also, the classification of economic potential and the possibilities of its use are highlighted, the directions of strategic management are given.